Implementasi pendidikan karakter pada peserta didik melalui budaya sekolah - Efi Nur Amira; Ferry Irawan Saputra; Selly Pitia; Chanifudin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The formation of student personality is significantly influenced by character education in schools, which aims to instill moral, ethical, and social values in everyday life. This study aims to explore how school culture can effectively implement character education. The research employs a qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation studies. The findings reveal that a conducive school culture plays a crucial role in shaping students’ character. Consistent discipline, positive role modeling from teachers and staff, and well-structured extracurricular activities are key factors in character development. Furthermore, values such as integrity, responsibility, cooperation, and social awareness are embedded through routine school activities, including ceremonies, group work, and social programs. The integration of character education into school culture not only enhances students’ academic performance but also develops individuals with strong moral values and high competitiveness. Therefore, schools hold a strategic role in producing a generation that is not only intellectually competent but also possesses strong character to face global challenges